2017
DOI: 10.1007/s10534-017-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide inhibits hemotoxic activity of Elapidae venoms: potential role of heme

Abstract: Envenomation by hemotoxic enzymes continues to be a major cause of morbidity and mortality throughout the world. With regard to treatment, the gold standard to abrogate coagulopathy caused by these venoms is still the administration of antivenom; however, despite antivenom therapy, coagulopathy still occurs and recurs. Of interest, this laboratory has demonstrated in vitro and in vivo that coagulopathy inducing venom derived from snakes of the family Viperidae exposed to carbon monoxide (CO) is inhibited, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(72 citation statements)
references
References 22 publications
2
70
0
Order By: Relevance
“…While the coagulopathic effects of hemotoxic venoms derived from venomous snakes have been of great scientific interest for several decades [1], it is only recently that investigation has intensified on the effects of neurotoxic venoms on coagulation [2][3][4][5][6][7]. Specifically, utilizing the thrombelastograph, the effects of neurotoxic venoms containing proteolytic and lipolytic enzymes on human plasma-based coagulation or isolated human thrombin-fibrinogen systems have been defined in venoms obtained from snakes within the Elapidae and Viperidae families [2][3][4][5][6][7]. Of interest, the venoms containing neurotoxic phospholipase A 2 (PLA 2 ) that were investigated were found to have their anticoagulant effects inhibited by either specific phospholipase A 2 inhibitors or tricarbonyldichlororuthenium (II) dimer (CORM-2) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…While the coagulopathic effects of hemotoxic venoms derived from venomous snakes have been of great scientific interest for several decades [1], it is only recently that investigation has intensified on the effects of neurotoxic venoms on coagulation [2][3][4][5][6][7]. Specifically, utilizing the thrombelastograph, the effects of neurotoxic venoms containing proteolytic and lipolytic enzymes on human plasma-based coagulation or isolated human thrombin-fibrinogen systems have been defined in venoms obtained from snakes within the Elapidae and Viperidae families [2][3][4][5][6][7]. Of interest, the venoms containing neurotoxic phospholipase A 2 (PLA 2 ) that were investigated were found to have their anticoagulant effects inhibited by either specific phospholipase A 2 inhibitors or tricarbonyldichlororuthenium (II) dimer (CORM-2) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the concentration of CatroxMP-II used, the onset of coagulation had to be double and/or the velocity of clot formation half of plasma without CatroxMP-II addition to be acceptable for experimentation. The following elastic modulus-based parameters previously described (Nielsen 2018; Nielsen and Bazzell 2016, 2017; Nielsen et al 2016, 2018a, b; Nielsen and Losada 2017; Nielsen and Matika 2017) were determined: time to maximum rate of thrombus generation (TMRTG): this is the time interval (minutes) observed prior to maximum speed of clot growth; maximum rate of thrombus generation (MRTG): this is the maximum velocity of clot growth observed (dynes/cm 2 /second); and total thrombus generation (TTG, dynes/cm 2 ), the final viscoelastic resistance observed after clot formation. Data were collected for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently demonstrated that the hemotoxic venom activity of several species of snakes can be inhibited in vitro and in vivo by exposure to carbon monoxide (CO) via thrombelastography (Nielsen 2018; Nielsen and Bazzell 2016, 2017; Nielsen et al 2016, 2018a, b; Nielsen and Losada 2017; Nielsen and Matika 2017). Also of interest, an agent that causes metheme formation (Nielsen et al 2011a) used to identify fibrinogen as a heme binding protein (Nielsen et al 2011b) was demonstrated to decrease the prothrombotic activity of Oxyuranus microlepidotus venom (Nielsen et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations